ANALYSIS OF THE AMOUNT OF MARINE SUPPLIES FISHING BOAT IN BUNGUS FISHING PORT WEST SUMATRA PROVINCE - Jonny Zain; Pareng Rengi; Fajriati Fajriati (Berkala Perikanan Terubuk, 2021)
The need for fishing supplies is important for fishermen because it is very decisive in the success offishing operations. What are the factors that affect the amount of fishing supplies needed by fishingvessels and how does it relate to the number of fishing supplies needed by fishermen at the BungusFishing Port. The research was carried out from February to March 2021. The needs for fishing suppliesneeded by fishermen include fuel, water, ice and logistical needs in the form of food and others. Theresearch method used in this research is the survey method. Data analysis in this study used multicollinearity analysis and multiple regression analysis. By looking at the value of the correlationcoefficient, the coefficient of determination, and the significance value (F test). The results showed thatall factors such as the size of the ship, the number of catches, the number of crew members, and the lengthof the fishing trip had an effect and had a positive relationship on the amount of fishing supplies neededby fishing vessels.